2012
DOI: 10.1093/nar/gks466
|View full text |Cite
|
Sign up to set email alerts
|

Myh7b/miR-499 gene expression is transcriptionally regulated by MRFs and Eos

Abstract: The sarcomeric myosin gene, Myh7b, encodes an intronic microRNA, miR-499, which regulates cardiac and skeletal muscle biology, yet little is known about its transcriptional regulation. To identify the transcription factors involved in regulating Myh7b/miR-499 gene expression, we have mapped the transcriptional start sites and identified an upstream 6.2 kb region of the mouse Myh7b gene whose activity mimics the expression pattern of the endogenous Myh7b gene both in vitro and in vivo. Through promoter deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Interestingly, in addition to lack of exercise influence over mir-499 quantities, we noted that this particular microRNA expresses in very low amounts in both the groups further downgrading its ability to mediate any physiological responses in skeletal muscles. In addition mir-499 expression might have very well diminished in differentiated matured muscles, as its expression is regulated by the myogenic transcriptional factors such as MyoD [50], suggesting its limited role during the muscle differentiation phase.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in addition to lack of exercise influence over mir-499 quantities, we noted that this particular microRNA expresses in very low amounts in both the groups further downgrading its ability to mediate any physiological responses in skeletal muscles. In addition mir-499 expression might have very well diminished in differentiated matured muscles, as its expression is regulated by the myogenic transcriptional factors such as MyoD [50], suggesting its limited role during the muscle differentiation phase.…”
Section: Discussionmentioning
confidence: 99%
“…The spatio-temporal expression of the major skeletal MYHs in teleost fish is regulated by small regions scattered throughout the 5′-flanking sequence [18,30,34,35]. Recently, Yeung et al [36] reported promoter activity in a 6.2-kb upstream sequence of mouse MYH14 that mimics endogenous MYH14 and miR-499 expression. Therefore, these conserved regions in the 5′-flanking sequence may act as a promoter for the spatio-temporal expression of MYH14 , and the regulatory sequences are conserved in medaka miR-499 despite the loss of the MYH14 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of binding sites for myogenic transcription factors in miRNA promoters, as well as the locations of some miRNA loci within introns of myogenic genes, result in highly regulated expression. For example, myogenic transcription factors that are known drivers of skeletal muscle specification and differentiation, including MyoD, myogenin and MYF5, bind to and activate the promoters of miR-206, miR-486 and miR-499 and the bicistronic miRNAs miR-1 and miR-133 (REFS 1418) (FIG. 3a).…”
Section: Mirnas In Myogenesismentioning
confidence: 99%